A low-absorption organic thermal control coating for magnesium alloy and preparation method thereof
By using the microarc oxidation process to form nanozirconium dioxide base coating and nanotitanium dioxide transparent sol gel surface coating in the spacecraft thermal control coating, the problem of high absorption and insufficient binding force of the existing thermal control coating is solved, and a thermal control coating with low absorption and high stability is achieved, meeting the high accuracy and high life requirements of the spacecraft.
Patent Information
- Application Number
- CN202410789959.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The existing thermally controlled coatings have problems in spacecraft with high absorption rate, unstable composition and insufficient binding force with substrates, which cannot meet the requirements of high stability and high life of the spacecraft.
A nanozirconium dioxide primer is formed on the surface of the substrate by microarc oxidation process, and a transparent sol gel coating with nanotitanium dioxide as the filler is used as the surface coating. Through the synergistic action of different nanofillers, the scattering ability and stability of the thermally controlled coating are significantly improved.
It has achieved an organic thermal control coating with ultra-low absorption rate, stable composition and good binding force with the substrate, meeting the design requirements of high precision, high stability and high life of the spacecraft, and has shown good corrosion resistance through salt spray tests.
Smart Images

Figure CN118791899B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment of thermal control materials, and in particular to a low-absorption organic thermal control coating for a magnesium alloy and a preparation method thereof. Background Art
[0002] Thermal control coatings mainly control the surface temperature of coatings by changing the two parameters of solar absorptivity and infrared emissivity on the surface of objects. They are one of the most commonly used thermal control materials in spacecraft thermal control systems. When a spacecraft reaches aphelion, the external solar radiation energy decreases, and the heat source mainly comes from internal components. Therefore, the temperature of the outer surface of the equipment is low, and the temperature of the inner surface is high, resulting in the problem of slow external heating and slow internal cooling of the material. When the spacecraft reaches perihelion, its heat source mainly comes from external space radiation, so the temperature of the outer surface of the equipment is high, resulting in rapid external heating of the material. The thermal control coating uses the surface thermophysical properties of the spacecraft to effectively control the temperature of the spacecraft during radiation heat exchange. Ultimately, during the internal and external heat exchange process, the operating temperature of internal equipment and instruments does not exceed the specified range, ensuring the normal operation of the spacecraft.
[0003] At present, there are two types of thermal control coatings used in domestic spacecraft. The first type is inorganic coatings such as anodic oxidation coatings and micro-arc oxidation coatings. The characteristics of the oxide layer material reduce the coating absorption rate, but the coating absorption rate is still high and cannot meet the high stability requirements of the new generation of spacecraft. The second type is the commonly used adhesive white coating or organic coating. Its advantage is that the coating absorption rate is low, and its disadvantage is that the coating or organic coating has insufficient bonding strength with the substrate, and the coating is prone to aging and falling off, which cannot meet the high life requirements of spacecraft.
[0004] Therefore, the research and development of organic thermal control coatings with ultra-low absorption rate, stable composition and good bonding with the substrate is an urgent need in the current stage of thermal control material development. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a magnesium alloy low-absorption organic thermal control coating with ultra-low absorption rate, stable composition and good bonding with a substrate and a preparation method thereof.
[0006] In order to solve the above technical problems, the present invention provides a low-absorption organic thermal control coating for magnesium alloy, comprising a base coating formed by a micro-arc oxidation coating and a top coating formed by a transparent sol-gel coating;
[0007] The base coating layer uses nano zirconium dioxide as the coating filler, the zirconium dioxide has an ellipsoidal morphology, a particle size of 200 to 500 nm, and a purity of ≥99.9%;
[0008] The surface coating layer selects nano titanium dioxide as coating filler, the titanium dioxide has a spherical shape, a filler particle size of 100-200nm, and a purity of ≥99.9%.
[0009] Furthermore, the thickness of the primer layer is 20 to 30 μm, and the thickness of the top coating layer is 40 to 50 μm.
[0010] The present invention also provides a method for preparing a magnesium alloy low-absorption organic thermal control coating, comprising the following steps:
[0011] A micro-arc oxidation process is used to form a micro-arc oxidation coating with nano zirconium dioxide as a dopant on the surface of the substrate as a base coating;
[0012] The nano-titanium dioxide powder is dispersed in an oily wetting dispersant, and then a sol-gel solution is added and mixed to obtain a coating-transparent sol-gel solution with the nano-titanium dioxide as a filler;
[0013] The coating-transparent sol-gel solution is sprayed on the surface of the base coating of the substrate and cured to obtain a low-absorption organic thermal control coating.
[0014] Furthermore, the zirconium dioxide has an ellipsoidal shape, a particle size of 200 to 500 nm, and a purity of ≥99.9%.
[0015] Furthermore, the titanium dioxide has a spherical shape, a filler particle size of 100 to 200 nm, and a purity of ≥99.9%.
[0016] Furthermore, the thickness of the primer layer is 20 to 30 μm, and the thickness of the top coating layer is 40 to 50 μm.
[0017] Furthermore, the micro-arc oxidation process comprises:
[0018] The substrate and graphite are placed in the electrolyte of a stainless steel electrolytic cell and connected to the anode and cathode of a micro-arc oxidation power supply respectively, and micro-arc oxidation electrolysis is performed to prepare a primer layer on the surface of the substrate.
[0019] Furthermore, the electrolyte includes 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia water, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol, and 15-20 g / L nano zirconium dioxide.
[0020] Furthermore, the current density of the micro-arc oxidation process is 4 to 6 A / dm 2 , frequency 100~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430V~450V.
[0021] Furthermore, in the micro-arc oxidation process, an electrically controlled stirrer is installed in the stainless steel electrolytic cell, and the stirring speed is 350-450 r / min. Indirect cooling is adopted in the stainless steel electrolytic cell, and the cooling temperature is controlled at 20-30°C.
[0022] Furthermore, the method for preparing the sol-gel solution includes:
[0023] Adding 3-glycidyloxypropyltrimethoxysilane to the ethanol aqueous solution and mixing well to obtain a first sol;
[0024] Add ethyl acetoacetate to anhydrous ethanol, then add ethyl orthosilicate, add glacial acetic acid to adjust the pH value, and mix well to obtain a second sol;
[0025] The second sol is added dropwise to the first sol, and a surfactant and a defoamer are added and mixed to obtain a sol-gel solution.
[0026] Furthermore, the surfactant is sodium dodecylbenzenesulfonate or mercaptobenzothiazole, and the defoaming agent is one or more of trialkyl melamine, fatty acid glyceride, and polymerized propylene oxide.
[0027] Furthermore, the substrate material is Mg-Li, AM50 or AZ91.
[0028] The present invention provides a magnesium alloy low-absorption organic thermal control coating, which includes a primer layer formed by a micro-arc oxidation coating and a top coating formed by a transparent sol-gel coating. Since the transparent sol-gel coating has the good properties of high hydrophobicity, good adhesion and high transparency, it can be tightly combined with the primer layer formed by the micro-arc oxidation coating and the substrate at the same time, thereby solving the problem of insufficient bonding between the organic coating and the substrate and easy aging and falling off of the coating.
[0029] In addition, the present invention provides a low-absorption organic thermal control coating for magnesium alloys, wherein the base coating layer selects nano zirconium dioxide with an ellipsoidal shape, a particle size of 200-500nm, and a purity of ≥99.9% as the coating filler. Since the nano zirconium dioxide particles have a high band gap energy, they can significantly reduce the coating's absorption of visible light and near-infrared light as the base coating filler. Meanwhile, the top coating layer selects nano titanium dioxide with a spherical shape, a particle size of 100-200nm, and a purity of ≥99.9% as the coating filler. Since the titanium dioxide nano titanium dioxide particles have a high reflectivity and a wide band gap width, they can effectively reflect ultraviolet light and effectively reduce the optical path of ultraviolet light inside the coating.
[0030] Therefore, the magnesium alloy low-absorption organic thermal control coating provided by the present invention can significantly improve the thermal control coating's scattering ability of sunlight and its stability under ultraviolet irradiation through the synergistic effect of different nanofillers in the base coating and the top coating, so that it can meet the current design requirements of high precision, high stability and long life of spacecraft.
[0031] At the same time, the method for preparing the low-absorption organic thermal control coating for magnesium alloy provided by the present invention has a simple process flow, readily available raw materials, low requirements on preparation conditions, is easy to prepare, has low cost, is economical and efficient, and the prepared low-absorption organic thermal control coating is white as a whole, the coating surface is uniform, without cracks or bubbles; the coating has an absorptivity of 0.1 to 0.15, and an emissivity of 0.85 to 0.9; the coating is subjected to a salt spray test for 30 days, and the coating has no corrosion or shedding phenomenon, and has good thermal control performance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A flow chart of a method for preparing a low-absorption organic thermal control coating for magnesium alloy provided in an embodiment of the present invention;
[0033] Figure 2 The macroscopic morphology comparison diagram of the thermal control coating prepared with Mg-Li alloy as the substrate provided in the comparative example of the present invention and Example 1; wherein (a) is the morphology diagram of PEO, and (b) is the morphology diagram of PEO-ZrO 2 (c) is the morphology of PEO-ZrO 2 -SG-TiO 2 The morphology diagram;
[0034] Figure 3 A comparison chart of the absorptivity of a low-absorption organic thermal control coating prepared with Mg-Li alloy as a substrate provided in the comparative example of the present invention and in Example 1;
[0035] Figure 4 A macroscopic morphology of a sol-gel solution prepared in a method for preparing a low-absorption organic thermal control coating for a magnesium alloy provided in Example 1 of the present invention;
[0036] Figure 5 This is a macroscopic morphology of a coating formed by spraying a sol-gel solution prepared in a method for preparing a low-absorption organic thermal control coating for a magnesium alloy provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] An embodiment of the present invention provides a magnesium alloy low-absorption organic thermal control coating, comprising a base coating formed by a micro-arc oxidation coating and a top coating formed by a transparent sol-gel coating;
[0038] The base coating layer uses nano zirconium dioxide as the coating filler, the zirconium dioxide has an ellipsoidal morphology, a particle size of 200 to 500 nm, and a purity of ≥99.9%;
[0039] The surface coating layer selects nano titanium dioxide as coating filler, the titanium dioxide has a spherical shape, a filler particle size of 100-200nm, and a purity of ≥99.9%.
[0040] Wherein, the thickness of the primer layer is 20-30 μm, and the thickness of the top layer is 40-50 μm.
[0041] See also Figure 1 The present invention provides a method for preparing a magnesium alloy low-absorption organic thermal control coating, comprising the following steps:
[0042] Step 1) A micro-arc oxidation coating with nano zirconium dioxide as a dopant is formed on the surface of the substrate as a base coating by using a micro-arc oxidation process.
[0043] Among them, in the micro-arc oxidation process, the substrate and the graphite plate are placed in the electrolyte of a stainless steel electrolytic cell, the substrate is connected to the anode end of the micro-arc oxidation power supply, and the graphite plate is connected to the cathode end of the micro-arc oxidation power supply, and micro-arc oxidation electrolysis is performed to form a layer of micro-arc oxidation coating on the surface of the substrate as a primer.
[0044] The substrate material is Mg-Li, AM50 or AZ91. In addition, before micro-arc oxidation, the substrate is first polished with 240#, 600#, and 1000# sandpaper for 20 minutes, then immersed in ethanol for 10 minutes, and finally blown dry with ethanol on the surface for standby use.
[0045] The electrolyte has a formula of 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol, and 15-20 g / L nano zirconium dioxide. After the electrolyte is added to the stainless steel electrolytic cell, ammonia is added to the electrolyte, and the pH value of the electrolyte is continuously measured to control the pH value of the electrolyte at 13.5-13.8.
[0046] The concentration of the ammonia water is 5wt.% to 10wt.%.
[0047] Among them, the pentylhexanol is high-grade pure pentylhexanol, and 30-50 ml / L of pentylhexanol can be replaced by 40-50 ml / L of high-grade pure n-butanol, or can be replaced by 30-40 ml / L of high-grade pure glycerol.
[0048] Among them, nano zirconium dioxide has an ellipsoidal shape, a particle size of 200-500nm, and a purity of
[0049] ≥99.9%.
[0050] Among them, the current density of the micro-arc oxidation process is 4 to 6A / dm 2 , frequency 100~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430V~450V.
[0051] During the micro-arc oxidation process, an electrically controlled stirrer is installed in the stainless steel electrolytic cell to stir the electrolyte at a stirring speed of 350-450r / min. At the same time, indirect cooling is used in the stainless steel electrolytic cell, and the cooling temperature is controlled at 20-30°C.
[0052] After the micro-arc oxidation electrolysis of the substrate is completed, a micro-arc oxidation coating with nano zirconium dioxide as a dopant is formed on the surface of the substrate. The micro-arc oxidation coating is used as a base coating of the thermal control coating of the substrate, and its thickness is 20-30 μm.
[0053] Since nano zirconium dioxide with an ellipsoidal shape, a particle size of 200-500nm, and a purity of ≥99.9% is added to the electrolyte, a nano zirconium dioxide filler with an ellipsoidal shape, a particle size of 200-500nm, and a purity of ≥99.9% is formed in the base coating. Since nano zirconium dioxide particles have a high band gap energy, they can significantly reduce the absorption of visible light and near-infrared light by the coating as a base coating filler.
[0054] Step 2) dispersing nano titanium dioxide powder in an oily wetting dispersant, then adding a transparent sol-gel solution, and mixing to obtain a coating-transparent sol-gel solution with nano titanium dioxide as filler;
[0055] Specifically, 5 to 8 ml of an oily wetting dispersant is added to 20 to 30 g of nano titanium dioxide powder to evenly disperse the nano titanium dioxide powder, and then the evenly dispersed nano titanium dioxide powder is poured into 100 to 150 ml of a transparent sol-gel solution, and the solution is evenly mixed using a stirring ball mill to finally obtain a sol-gel solution with nano titanium dioxide as filler.
[0056] The titanium dioxide powder is spherical in shape, with a filler particle size of 100 to 200 nm and a purity of ≥99.9%.
[0057] Wherein, the transparent sol-gel solution is obtained by the following method:
[0058] First, 3-glycidyloxypropyltrimethoxysilane is added to an ethanol aqueous solution and mixed to obtain a first sol.
[0059] Then, ethyl acetoacetate is added to anhydrous ethanol, followed by ethyl orthosilicate, and glacial acetic acid is added to adjust the pH value, and the mixture is mixed to obtain a second sol.
[0060] Finally, the second sol is added dropwise to the first sol, and a surfactant and a defoamer are added and mixed to obtain a transparent sol-gel solution.
[0061] Wherein, the surfactant is sodium dodecylbenzene sulfonate or mercaptobenzothiazole, and the defoaming agent is one or more of trialkyl melamine, fatty acid glyceride, and polymerized propylene oxide.
[0062] The preparation of each transparent sol-gel solution requires 30-40 ml of anhydrous ethanol, 24-30 ml of 3-glycidyloxypropyltrimethoxysilane, 6-10 ml of ethyl acetoacetate, 12-18 ml of tetraethyl orthosilicate, 1.2-2 ml of glacial acetic acid, 5-10 g of sodium dodecylbenzene sulfonate, and 5-10 ml of defoaming agent.
[0063] Specifically, the sol-gel solution is configured as follows:
[0064] (1) Prepare the first sol: add 14-20 ml of deionized water to 30-40 ml of anhydrous ethanol, stir with a glass rod for a while, then slowly add 24-30 ml of 3-glycidyloxypropyltrimethoxysilane, add a magnetic stir bar, seal the beaker with plastic wrap, and stir on a stirrer for 1-2 hours.
[0065] (2) Prepare the second sol: add 6-10 mL of ethyl acetoacetate to 12-20 mL of anhydrous ethanol, then slowly add 12-20 mL of tetraethyl orthosilicate. To adjust the pH value, add 1.2-2 mL of glacial acetic acid. Place a magnetic stirrer, seal the beaker with plastic wrap, and stir for 1-2 h.
[0066] (3) After stirring, the prepared second sol is dripped into the first sol with a dropper, and 5-10 g of sodium dodecylbenzene sulfonate and 5-10 mL of defoaming agent are added and stirred for 30 minutes. The sol-gel solution is prepared.
[0067] Among them, 24-30 mL of 3-glycidyloxypropyltrimethoxysilane can be replaced by 24-30 mL of γ-glycidyloxypropyltrimethoxysilane.
[0068] Wherein, 5-10g of sodium dodecylbenzenesulfonate can be replaced by 5-10g of mercaptobenzothiazole.
[0069] Step 3) spraying the coating-transparent sol-gel solution on the surface of the base coating of the substrate, and curing to obtain a low-absorption organic thermal control coating.
[0070] Specifically, a coating-transparent sol-gel solution with nano titanium dioxide as filler is placed in a spray gun and sprayed on the surface of the base coating of the substrate one by one, and then cured at room temperature for 10 to 12 hours to form a top coating on the surface of the base coating of the substrate, thereby preparing the low-absorption organic thermal control coating.
[0071] The thickness of the top coating is 40 to 50 μm.
[0072] Since the top coating uses nano-titanium dioxide with a spherical shape, a particle size of 100-200nm and a purity of ≥99.9% as the coating filler, and the nano-titanium dioxide particles have a high reflectivity and a wide bandgap width, they can effectively reflect ultraviolet light and effectively reduce the optical path of ultraviolet light inside the coating.
[0073] The low-absorption organic thermal control coating for magnesium alloy prepared by the present invention can significantly improve the scattering ability of the thermal control coating for sunlight and the stability under ultraviolet irradiation through the synergistic effect of different nanofillers in the base coating and the top coating.
[0074] The low-absorption organic thermal control coating of magnesium alloy prepared by the present invention has the following characteristics.
[0075] 1) Macro morphology: The coating is white as a whole, with a uniform surface, no cracks, and no bubbles.
[0076] 2) Thermal control performance: absorptivity is 0.1~0.15, emissivity is 0.85~0.9.
[0077] 3) Corrosion performance: After 30 days of salt spray test, the coating showed no corrosion or shedding.
[0078] Therefore, the low-absorption organic thermal control coating of magnesium alloy prepared by the present invention can meet the design requirements of high precision, high stability and long life of current spacecraft.
[0079] The following comparative examples and embodiments specifically illustrate the method for preparing a low-absorption organic thermal control coating for magnesium alloy provided by the present invention.
[0080] Comparative Example
[0081] The primer layer is prepared on the surface of the Mg-Li alloy substrate, and the specific process is as follows.
[0082] 1. Substrate pretreatment: The Mg-Li alloy was polished with 240#, 600#, and 1000# sandpaper for 20 minutes respectively, and then immersed in an ethanol solution for 10 minutes. The surface ethanol was blown dry and dried for later use.
[0083] 2. Sample installation: Connect the pre-treated substrate to the anode end of the micro-arc oxidation power supply, connect the graphite plate to the cathode end of the micro-arc oxidation power supply, and place the substrate and the graphite plate on opposite sides of the electrolytic cell.
[0084] 3. Preparation of electrolyte: 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia water, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol are placed in an electrolytic cell, 10 ml / L ammonia water is added, and the pH value of the solution is measured to be above 12.5.
[0085] 4. Micro-arc oxidation power supply process parameter setting: current density 4~6A / dm 2 , frequency 200~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430~450V.
[0086] 5. During the preparation of the substrate primer layer, an electrically controlled stirrer was installed in the electrolytic cell with a stirring speed of 400 r / min. At the same time, indirect cooling was performed in the electrolytic cell with the cooling temperature set at 25°C. After the micro-arc oxidation was completed, the substrate coating was obtained.
[0087] Among them, the coating obtained by micro-arc oxidation using an electrolyte without nano zirconium dioxide in the comparative example is represented by PEO.
[0088] The substrate is taken out, and the coating on the substrate surface is washed and dried. The morphology of the substrate coating obtained is as follows: Figure 2 (a) shown.
[0089] from Figure 2 (a) It can be seen that the substrate coating prepared in this comparative example has a darker color, so the absorption rate of the coating is higher.
[0090] At this time, the absorption rate of the coating prepared on the substrate surface was measured, and its absorption rate value was as high as 0.47. Figure 3 As shown in PEO.
[0091] Example 1
[0092] The specific preparation method of the low-absorption organic thermal control coating of this embodiment includes the following steps:
[0093] 1. Preparation of base coating - micro-arc oxidation coating (relative to the comparative example, in Example 1 of the present invention, nano zirconium dioxide is added to the electrolyte used in micro-arc oxidation).
[0094] 1. Substrate pretreatment: The Mg-Li alloy was polished with 240#, 600#, and 1000# sandpaper for 20 minutes respectively, and then immersed in an ethanol solution for 10 minutes. The surface ethanol was blown dry and dried for later use.
[0095] 2. Sample installation: Connect the pre-treated substrate to the anode end of the micro-arc oxidation power supply, connect the graphite plate to the cathode end of the micro-arc oxidation power supply, and place the substrate and the graphite plate on opposite sides of the electrolytic cell.
[0096] 3. Preparation of electrolyte: 40-50g / L sodium metasilicate, 10-20ml / L ammonia water, 2-4g / L potassium fluoride, 4-6g / L potassium hydroxide, 30-50ml / L pentylhexanol, 15-20g / L nano zirconium dioxide are placed in an electrolytic cell, 10ml / L ammonia water is added, and the pH value of the solution is measured to be above 12.5.
[0097] 4. Micro-arc oxidation power supply process parameter setting: current density 4~6A / dm 2 , frequency 200~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430~450V.
[0098] 5. During the preparation of the substrate primer layer, an electrically controlled stirrer was installed in the electrolytic cell with a stirring speed of 400 r / min. At the same time, indirect cooling was performed in the electrolytic cell with the cooling temperature set at 25°C. After the micro-arc oxidation was completed, the substrate primer layer was obtained.
[0099] Among them, in this embodiment 1, the primer layer obtained by micro-arc oxidation using an electrolyte containing nano zirconium dioxide is PEO-ZrO 2 express.
[0100] The substrate is taken out, and the primer layer on the surface of the substrate is washed and dried. The morphology of the primer layer on the substrate is as follows: Figure 2 (b) as shown.
[0101] from Figure 2 (b) It can be seen that since the electrolyte formula of the embodiment of the present invention is improved and nano zirconium dioxide is added to the electrolyte, the morphology of the substrate primer coating obtained in this way is different from that of the substrate primer coating of the comparative example. Figure 2 (a) The color of the base coating layer prepared in the embodiment of the present invention has turned white, so the thermal control rate of the coating layer is reduced.
[0102] At this time, the absorbance value of the base coating prepared on the surface of the substrate was measured, and its absorbance value was 0.27. The absorbance graph of the coating is as follows Figure 3 PEO-ZrO 2 shown.
[0103] 2. Top coating - transparent sol-gel coating with nano titanium dioxide as filler.
[0104] 1. Preparation of transparent sol-gel solution for top coating:
[0105] (1) Prepare the first sol: add 14-20 ml of deionized water to 30-40 ml of anhydrous ethanol, stir with a glass rod for a while, then slowly add 24-30 ml of 3-glycidyloxypropyltrimethoxysilane, add a magnetic stir bar, seal the beaker with plastic wrap, and stir on a stirrer for 1-2 hours.
[0106] (2) Prepare the second sol: add 6-10 mL of ethyl acetoacetate to 12-20 mL of anhydrous ethanol, then slowly add 12-20 mL of tetraethyl orthosilicate. To adjust the pH value, add 1.2-2 mL of glacial acetic acid. Place a magnetic stirrer, seal the beaker with plastic wrap, and stir for 1-2 h.
[0107] (3) After stirring, the prepared second sol is dripped into the first sol with a dropper, and 5-10 g of sodium dodecylbenzene sulfonate and 5-10 mL of defoaming agent are added and stirred for 30 min. The sol-gel solution is prepared. The macroscopic morphology of the prepared sol-gel solution is shown in FIG. Figure 4 shown.
[0108] See also Figure 4 It can be seen that the sol-gel solution prepared in this embodiment is a transparent sol-gel solution. Therefore, after being doped with white powder, the transparent sol-gel solution can achieve color compatibility with the white powder and does not affect the overall thermal control performance of the coating.
[0109] In order to prove the stability of the coating formed by spraying the transparent sol-gel solution prepared in this example on a substrate, the transparent sol-gel solution prepared in this example was sprayed on a polished, washed and dried Mg-Li alloy substrate, and then cured to obtain a coating formed by the transparent sol-gel solution. The macroscopic morphology of the coating formed by spraying the transparent sol-gel solution is shown in FIG. Figure 5 shown.
[0110] from Figure 5 It can be seen that there is no sign of yellowing on the coating surface, and there are no bubbles, cracks or other defects on the coating surface. Therefore, the transparent sol-gel solution prepared in the embodiment of the present invention can be used in combination with other base coatings to reduce the overall absorption rate of the coating.
[0111] (4) Add 5 to 8 ml of an oily wetting dispersant to 20 to 30 g of nano-titanium dioxide powder to evenly disperse the powder. Pour the evenly dispersed nano-powder into 100 to 150 ml of a sol-gel solution and mix the solution evenly using a stirring ball mill to obtain a sol-gel solution with nano-titanium dioxide as filler.
[0112] When preparing the top coating, nano titanium dioxide is selected as the transparent sol-gel coating filler. The titanium dioxide has a spherical shape, a filler particle size of 100-200nm, and a purity of ≥99.9%.
[0113] 2. Low-absorption organic thermal control coating for magnesium alloy: Place the sol-gel solution filler liquid with titanium dioxide filler in a spray gun and spray it on the surface of the base coating layer in succession. The spraying thickness should be 40 to 50 μm, and then cure it at room temperature for 10 to 12 hours to obtain a low-absorption organic thermal control coating.
[0114] Among them, the low-absorption organic thermal control coating formed by the primer and top coating prepared in Example 1 is made of PEO-ZrO 2 -SG-TiO 2 express.
[0115] The coating morphology of the low-absorption organic thermal control coating prepared in the embodiment of the present invention is as follows: Figure 2 (c) as shown.
[0116] from Figure 2 (c) It can be seen that the embodiment of the present invention further coats a sol-gel coating with nano titanium dioxide as filler on the substrate base coating as a top coating, indicating that the transparent sol-gel solution used in the embodiment of the present invention has good compatibility with the doping material titanium dioxide. The top coating after coating is already very white in color and has no yellowing signs. The coating surface is uniform and has no blistering. Therefore, the low-absorption rate organic thermal control coating prepared in the embodiment of the present invention will have a very low thermal control rate.
[0117] The absorbance value of the low-absorption organic thermal control coating prepared in the embodiment of the present invention was measured, and the absorbance value was as low as 0.1.
[0118] The coating absorption rate is shown in the figure Figure 3 PEO-ZrO 2 -SG-TiO 2 shown.
[0119] pass Figure 3 From the comparison of the absorption rate values of the coatings, it can be seen that the low absorption rate organic thermal control coating finally prepared in Example 1 of the present invention has a synergistic effect of different nanofillers in the base coating and the top coating, which can significantly improve the scattering ability of the coating to sunlight, thereby reducing the absorption rate of the coating.
[0120] It has been measured that the emissivity of the low-absorption organic thermal control coating prepared in the embodiment of the present invention is 0.88.
[0121] Example 2
[0122] The specific preparation method of the low-absorption organic thermal control coating of this example includes the following steps:
[0123] Preparation of base coating-micro-arc oxidation coating.
[0124] Substrate pretreatment: AM50 alloy was polished with 240#, 600#, and 1000# sandpaper for 20 minutes respectively, then immersed in ethanol for 10 minutes, and the surface ethanol was blown dry and dried for later use.
[0125] Sample installation: connect the pre-treated substrate to the anode end of the micro-arc oxidation power supply, connect the graphite plate to the cathode end of the micro-arc oxidation power supply, and place the substrate and the graphite plate on opposite sides of the electrolytic cell.
[0126] Preparation of electrolyte: 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia water, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol, 15-20 g / L nano zirconium dioxide are placed in an electrolytic cell, 10 ml / L ammonia water is added, and the pH value of the solution is measured to be above 12.5.
[0127] Micro-arc oxidation power supply process parameter setting: current density 4~6A / dm 2 , frequency 200~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430~450V.
[0128] During the preparation of the substrate, an electrically controlled stirrer was installed in the electrolytic cell with a stirring speed of 400 r / min. At the same time, indirect cooling was performed in the electrolytic cell with the cooling temperature set at 25° C. After the micro-arc oxidation was completed, the substrate primer layer was obtained.
[0129] Top coating - transparent sol-gel coating with titanium dioxide as filler.
[0130] Preparation of coating-transparent sol-gel solution for topcoat:
[0131] (1) Prepare the first sol: add 14-20 ml of deionized water to 30-40 ml of anhydrous ethanol, stir with a glass rod for a while, then slowly add 24-30 ml of 3-glycidyloxypropyltrimethoxysilane, add a magnetic stir bar, seal the beaker with plastic wrap, and stir on a stirrer for 1-2 hours.
[0132] (2) Prepare the second sol: add 6-10 mL of ethyl acetoacetate to 12-20 mL of anhydrous ethanol, then slowly add 12-20 mL of tetraethyl orthosilicate. To adjust the pH value, add 1.2-2 mL of glacial acetic acid. Place a magnetic stirrer, seal the beaker with plastic wrap, and stir for 1-2 h.
[0133] (3) After stirring, the prepared second sol is dripped into the first sol with a dropper, and 5-10 g of sodium dodecylbenzene sulfonate and 5-10 mL of defoaming agent are added and stirred for 30 minutes. The sol-gel solution is prepared.
[0134] (4) Add 5 to 8 ml of an oily wetting dispersant to 20 to 30 g of nano-titanium dioxide powder to evenly disperse the powder, then pour the evenly dispersed nano-powder into 100 to 150 ml of a sol-gel solution, use a stirring ball mill to evenly mix the solution, and finally obtain a sol-gel solution with nano-titanium dioxide as filler.
[0135] When preparing the top coating, nano titanium dioxide is selected as the transparent sol-gel coating filler. The titanium dioxide has a spherical shape, a filler particle size of 100-200nm, and a purity of ≥99.9%.
[0136] Preparation of the top coating: Place a sol-gel solution filler containing nano-titanium dioxide filler in a spray gun and spray it on the surface of the base coating layer in succession. The spraying thickness is preferably 40 to 50 μm, and then cure it at room temperature for 10 to 12 hours to obtain the low-absorption organic thermal control coating.
[0137] The organic thermal control coating prepared in the embodiment of the present invention has an absorptivity of 0.15 and an emissivity of 0.86.
[0138] Example 3
[0139] The specific preparation method of the low-absorption organic thermal control coating of this example includes the following steps:
[0140] Preparation of base coating-micro-arc oxidation coating.
[0141] Substrate pretreatment: AZ91 alloy was polished with 240#, 600#, and 1000# sandpaper for 20 minutes respectively, then immersed in ethanol for 10 minutes, and the surface ethanol was blown dry and dried for later use.
[0142] Sample installation: connect the pre-treated substrate to the anode end of the micro-arc oxidation power supply, connect the graphite plate to the cathode end of the micro-arc oxidation power supply, and place the substrate and the graphite plate on opposite sides of the electrolytic cell.
[0143] Preparation of electrolyte: 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia water, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol, 15-20 g / L nano zirconium dioxide are placed in an electrolytic cell, 10 ml / L ammonia water is added, and the pH value of the solution is measured to be above 12.50.
[0144] Micro-arc oxidation power supply process parameter setting: current density 4~6A / dm 2 , frequency 200~300Hz, duty cycle 20~40%, processing time 10~15min, temperature 25~35℃, given voltage upper limit range 430~450V.
[0145] During the preparation of the substrate, an electrically controlled stirrer was installed in the electrolytic cell with a stirring speed of 400 r / min. At the same time, indirect cooling was performed in the electrolytic cell with the cooling temperature set at 25° C. After the micro-arc oxidation was completed, the substrate primer layer was obtained.
[0146] Top coating - transparent sol-gel coating with nano-titanium dioxide as filler.
[0147] Preparation of coating-transparent sol-gel solution for topcoat:
[0148] (1) Prepare the first sol: add 14-20 ml of deionized water to 30-40 ml of anhydrous ethanol, stir with a glass rod for a while, then slowly add 24-30 ml of 3-glycidyloxypropyltrimethoxysilane, add a magnetic stir bar, seal the beaker with plastic wrap, and stir on a stirrer for 1-2 hours.
[0149] (2) Prepare the second sol: add 6-10 mL of ethyl acetoacetate to 12-20 mL of anhydrous ethanol, then slowly add 12-20 mL of tetraethyl orthosilicate. To adjust the pH value, add 1.2-2 mL of glacial acetic acid. Place a magnetic stirrer, seal the beaker with plastic wrap, and stir for 1-2 h.
[0150] (3) After stirring, the prepared second sol is dripped into the first sol with a dropper, and 5-10 g of sodium dodecylbenzene sulfonate and 5-10 mL of defoaming agent are added and stirred for 30 minutes. The sol-gel solution is prepared.
[0151] (4) Add 5 to 8 ml of an oily wetting dispersant to 20 to 30 g of nano-titanium dioxide powder to evenly disperse the powder, then pour the evenly dispersed nano-powder into 100 to 150 ml of a sol-gel solution, use a stirring ball mill to evenly mix the solution, and finally obtain a sol-gel solution with nano-titanium dioxide as filler.
[0152] When preparing the top coating, titanium dioxide is selected as the transparent sol-gel coating filler. The titanium dioxide has a spherical shape, a filler particle size of 100-200nm, and a purity of ≥99.9%.
[0153] Preparation of the top coating: Place a sol-gel solution with titanium dioxide as filler in a spray gun and spray it on the surface of the base coating in succession. The spraying thickness is preferably 40 to 50 μm, and then cure it at room temperature for 10 to 12 hours to obtain the low absorption rate organic thermal control coating.
[0154] The organic thermal control coating prepared in the embodiment of the present invention has an absorptivity of 0.11 and an emissivity of 0.89.
[0155] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a low-absorption organic thermal control coating for a magnesium alloy, characterized in that: The steps include: A micro-arc oxidation coating with nano zirconium dioxide as a dopant is formed on the surface of a substrate as a bottom coating by adopting a micro-arc oxidation process; in the micro-arc oxidation process, the substrate and the graphite plate are placed in an electrolyte of a stainless steel electrolytic cell, the substrate is connected to the anode end of a micro-arc oxidation power supply, the graphite plate is connected to the cathode end of a micro-arc oxidation power supply, and micro-arc oxidation electrolysis is performed to form a layer of micro-arc oxidation coating on the surface of the substrate as a bottom coating; 5 to 8 ml of an oily wetting dispersant is added to 20 to 30 g of nano titanium dioxide powder to evenly disperse the nano titanium dioxide powder, and then the evenly dispersed nano titanium dioxide powder is poured into 100 to 150 ml of a transparent sol-gel solution, and the solution is evenly mixed by a stirring ball mill to obtain a coating-transparent sol-gel solution with nano titanium dioxide as a filler, i.e., a top coating; the coating-transparent sol-gel solution is sprayed on the bottom coating surface of the substrate, and cured to obtain a low-absorption organic thermal control coating; The base coating layer uses nano zirconium dioxide as the coating filler, the zirconium dioxide morphology is ellipsoidal, the particle size is 200-500nm, and the purity is ≥99.9%, the top coating layer uses nano titanium dioxide as the coating filler, the titanium dioxide morphology is spherical, the filler particle size is 100-200nm, and the purity is ≥99.9%, the base coating layer has a thickness of 20-30μm, and the top coating layer has a thickness of 40-50μm; The electrolyte includes 40-50 g / L sodium metasilicate, 10-20 ml / L ammonia water, 2-4 g / L potassium fluoride, 4-6 g / L potassium hydroxide, 30-50 ml / L pentylhexanol, and 15-20 g / L nano zirconium dioxide; the current density of the micro-arc oxidation process is 4-6 A / dm 2 , frequency 100-300Hz, duty cycle 20-40%, processing time 10-15min, temperature 25-35°C, given voltage upper limit range 430V-450V; an electrically controlled stirrer is installed in the stainless steel electrolytic cell, the stirring speed is 350-450r / min, indirect cooling is adopted in the stainless steel electrolytic cell, and the cooling temperature is controlled at 20-30°C; The preparation method of the sol-gel solution comprises: adding 3-glycidyloxypropyltrimethoxysilane to an ethanol aqueous solution, and mixing to obtain a first sol; adding ethyl acetoacetate to anhydrous ethanol, and then adding tetraethyl orthosilicate, and adding glacial acetic acid to adjust the pH value, and mixing to obtain a second sol; dropping the second sol into the first sol, adding a surfactant and a defoaming agent, and mixing to obtain a sol-gel solution; The absorptivity of the organic thermal control coating is between 0.1 and 0.15, and the emissivity is between 0.85 and 0.
9.
2. The method for preparing a magnesium alloy low-absorption organic thermal control coating according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate, and the defoaming agent is trialkyl melamine.
3. The method for preparing a magnesium alloy low-absorption organic thermal control coating according to claim 1, characterized in that: The substrate is Mg-Li, AM50 or AZ91.
Citation Information
Patent Citations
Method for preparing low-absorptance high-emissivity thermal control coating on magnesium alloy surface through micro-arc oxidation technology
CN105442020A
Preparation method for magnesium alloy micro-arc oxidation-sol-gel composite coating
CN107460453A